Bibliometric Analysis of Worldwide Publications on Antimalarial Drug Resistance (2006–2015). (10th August 2017) - Sweileh, Waleed M.; Al-Jabi, Samah W.; Sawalha, Ansam F.; AbuTaha, Adham S.; Zyoud, Sa'ed H.
Abstract : Background. In response to international efforts to control and eradicate malaria, we designed this study to give a bibliometric overview of research productivity in antimalarial drug resistance (AMDR). Methods. Keywords related to AMDR were used to retrieve relevant literature using Scopus database. Results. A total of 976 publications with an h-index of 63 were retrieved. The number of publications showed a noticeable increase starting in the early 1990s. The USA was the most productive country with 337 publications equivalent to one-third of worldwide publications in this field. More than two-thirds of publications by the USA (236, 70.03%) were made by international collaboration. Of the top ten productive countries, two countries were from Mekong subregion, particularly Thailand and Cambodia. The Malaria Journal was the most productive journal (136, 13.93%) in this field. Mahidol University (80, 8.20%) in Thailand was the most productive institution. Seven articles in the top-ten list were about artemisinin resistance in Plasmodium falciparum, one was about chloroquine resistance, one was about sulfadoxine-pyrimethamine resistance, and the remaining one was about general multidrug resistance. Conclusion. Eradication and control of AMDR require continuing research activity to help international health organizations identify spots that require an immediate action to implement appropriate measures.